Procedures of Democratic Participation in Synodality in the Life and Mission of the Church - Szaniszló, Inocent-Mária V. (Asian Horizons, 2020)
International Theological Commission (ITC) published in 2018 a document entitled Synodality in the Life and Mission of the Church, which, in accordance with the ideas of Pope Francis on the occasion of the 50th anniversary of the Institution of the Synod of Bishops, develops the ancient idea of a synodal understanding of the Church as a way of dialogue, solidarity and social diakonia. The document notes the practice of dialogue and the search for effective joint solutions by which we commit ourselves to peace and justice like an absolute priority in a situation where there is a structural crisis in the procedures of democratic participation and a loss of confidence in its principles and inspirational values, with the threat of authoritarian and technocratic aberrations. For this reason, in our paper, we would like to address these procedures by looking for a place of the Church in the social life with a help of several important Catholic thinkers.